Oral preparation containing chicory dietary fiber or cassava starch
By using chicory dietary fiber or cassava starch that removes linamarin as an adhesion layer, combining bad breath inhibitors and saliva secretion promoters to form a double-layer preparation, the problems of high irritation and insufficient adhesion in the prior art are solved, and the effects of high adhesion and long-term use are achieved.
Patent Information
- Application Number
- CN202380065278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-04
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-18
AI Technical Summary
During use, existing oral preparations are prone to ionic interactions with the oral mucosa, resulting in high irritation and insufficient adhesion, making it difficult to remain in the oral cavity for a long time.
Chicory dietary fiber or cassava starch that removes linamarin as the adhesion layer component, and contains a bad breath inhibitor and saliva secretion promoter in the efficacy layer to form a bilayer formulation, and silica is used as an excipient to improve adhesion and strength.
It achieves the maintenance of high adhesion and long-term use without irritating the oral mucosa, effectively inhibiting bad breath and promoting saliva secretion.
Smart Images

Figure CN119855582A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an oral mucosal preparation comprising an adhesive layer and an efficacy layer, and relates to an oral preparation having low irritation to the oral mucosa and excellent adhesion, wherein the adhesive layer comprises a mixture of chicory dietary fiber or cassava starch from which linamarin is removed, and the efficacy layer comprises efficacy ingredients for the purpose of removing or alleviating bad breath. Background Art
[0002] Bad breath refers to an unpleasant odor in the mouth. Although it is not a disease that causes pain to the patient, it occurs when breathing, talking, and chewing, which can have a negative impact on interpersonal relationships. As a result, it develops into a factor that causes psychological atrophy and hinders normal social life, and patients with this disease feel a lot of inconvenience. Less than 10% of cases of digestive organ diseases such as the stomach and intestines are caused by bad breath. 90% of bad breath problems are caused by the decomposition of proteins in food remaining in the mouth, oral cells, or proteins in saliva, etc., which produce hydrogen sulfide (H2S). 2 S), methyl mercaptan (CH 3 SH) and dimethyl sulfide ((CH 3 ) 2 S) and other volatile sulfur compounds (VSCs) produced by Gram-negative anaerobic bacteria.
[0003] Environmental conditions that are prone to causing bad breath include poor oral hygiene caused by food residue between teeth or in dental aids such as dentures, and oral inflammatory diseases such as periodontitis and tonsillitis. In addition, factors that reduce saliva secretion, such as smoking, sleep, fasting, and dry mouth, also increase the number of bad breath-causing bacteria in the mouth. Therefore, as a solution to improve bad breath, in addition to removing the cause of reduced saliva secretion such as smoking, there are also solutions such as taking saliva secretion-promoting ingredients, neutralizing VSCs, and inhibiting the activity of bad breath pathogens.
[0004] Xylitol, a well-known sweetener that replaces sugar, inhibits the production of acid and energy from Streptococcus mutans (S. mutans) and has not only an effect of reducing S. mutans but also an effect of promoting saliva secretion. 2+ ) and copper ions (Cu 2+ ) In addition, several metal ions 2- and CH 3 S -The strong binding force of such sulfides has the effect of preventing the formation of VSCs. In addition, zinc ions (Zn) can inhibit the formation of bad breath pathogens such as Porphyromonas gingivalis (P.gingivalis), Fusobacterium nucleatum (F.nucleatum), Tannerella forsythia (T.forsythus), Prevotella intermedia (P.intermedia), and Prevotella nigrescens (P.nigrescens). 2+ ) In addition to the VSCs neutralization effect, some metal ions have an antibacterial effect. Therefore, products containing such ingredients for reducing bad breath are known, and the effect is increased when the antibacterial and saliva-increasing active ingredients are continuously released in the oral cavity.
[0005] Thus, various products are known that are made into chewing gum, candy and other forms of products containing oral health-improving effective ingredients, and release their ingredients in the oral cavity for a long time when the consumer ingests them, but their sustained release time is about 5 minutes to a maximum of about 15 minutes, so it is somewhat insufficient. As a countermeasure to this, preparations containing adhesive components such as carboxymethyl cellulose (CMC), carbopol (Carbopol, polyacrylic acid), polyvinyl pyrrolidone (PVP), etc. have been developed, and products in the form of patches or tablets that can be used for a longer time than existing products when attached to a specific position in the oral cavity are known. However, CMC, carbopol or PVP, as synthetic polymers for adhesion, produce ionic interactions with the oral mucosa and cause problems of irritating the oral mucosa, thereby causing mucosal pain during use. As another approach, Arabic gum is known as a natural polymer for adhesion. However, since this natural polymer contains a carboxyl group (COOH group), there is still a problem of ionic interaction with the oral mucosa.
[0006] Furthermore, when a water curtain is formed on the mucosa when saliva is secreted excessively, the interaction between the adhesive polymer and the mucosa is reduced, and fixation is difficult. In view of this, it is necessary to develop a preparation that uses a polymer that does not produce ionic interaction and has an adhesive layer that maintains high adhesion to the oral mucosa even when saliva is secreted excessively.
[0007] In this context, the inventors disclosed an adhesive layer preparation containing chicory dietary fiber or cassava starch (tapioca flour) and silicon dioxide in order to solve the previous problems, and a double-layer preparation containing an effective ingredient for removing or alleviating bad breath and including an adhesive layer. That is, the present invention provides an improved preparation as follows: chicory dietary fiber or cassava starch that does not contain a carboxyl group (-COOH) and can show adhesion without generating ionic interactions with the oral mucosa as an adhesive polymer component, so that the adhesion is similar or superior to that of generally known adhesive polymers, and the irritation to the oral mucosa caused by long-term use of adhesive preparations to suppress or alleviate bad breath can be reduced. In addition, the following preparation is provided: when silicon dioxide is used as an excipient on the adhesive layer in a double-layer tablet, unlike other excipients, it shows higher adhesion to the oral mucosa, thereby improving the strength of the tableted preparation. Summary of the invention
[0008] Technical issues
[0009] The object of the present invention is to provide an oral preparation as follows: comprising: an adhesive layer, the adhesive layer comprising at least one selected from the group consisting of a mixture of cassava starch without linamarin and chicory dietary fiber; and an efficacy layer, the efficacy layer providing at least one function of halitosis suppression, saliva secretion promotion and antibacterial, and having excellent adhesion and low irritation to the oral mucosa.
[0010] Another object of the present invention is to provide an oral adhesive composition using, as an oral adhesive, at least one polymer selected from the group consisting of a mixture of tapioca starch from which linamarin has been removed and chicory dietary fiber.
[0011] Means for solving problems
[0012] To this, specific description is as follows. In addition, each description and embodiment disclosed in the present invention can also be applied to other descriptions and embodiments respectively. That is, all combinations of various elements disclosed in the present invention belong to the scope of the present invention. In addition, the scope of the present invention is not limited to the specific description recorded below.
[0013] According to one embodiment of the present invention, there is provided an oral preparation, comprising: an adhesive layer comprising an adhesive polymer; and a functional layer, wherein the adhesive polymer comprises at least one selected from the group consisting of a mixture of cassava starch with lina marin removed and chicory dietary fiber.
[0014] In addition, according to one embodiment of the present invention, the above-mentioned functional layer provides at least one function of suppressing bad breath, promoting saliva secretion, reducing dental plaque, reducing gingivitis, reducing periodontitis, alleviating periodontal diseases and alleviating dental caries.
[0015] In addition, according to one embodiment of the present invention, the oral preparation has a double-layer tablet form.
[0016] According to one embodiment of the present invention, the adhesive layer further comprises silicon dioxide as an excipient, and the oral preparation has any dosage form selected from the group consisting of a halitosis remover, a xerostomia improver, a solid oral cleaning agent, a solid toothpaste, and a sustained-release candy.
[0017] In addition, according to one embodiment of the present invention, the above excipient is included in an amount of 20 wt % to 40 wt % relative to the total weight of the adhesive layer raw material.
[0018] In addition, according to an embodiment of the present invention, the diameter of the silicon dioxide particles is not less than 1 nm and not more than 50 μm.
[0019] In addition, according to one embodiment of the present invention, the functional layer further comprises, as a bad breath inhibitor, an ion selected from the group consisting of copper ions (Cu 2+ ), zinc ion (Zn 2+ ) or tin ions (Sn 2+ ) is any one or more of the group consisting of salts thereof.
[0020] In addition, according to an embodiment of the present invention, the efficacy layer contains the oral malodor suppressant in an amount of 0.1 wt % to 5 wt % relative to the total weight.
[0021] In addition, according to one embodiment of the present invention, the efficacy layer comprises 50 wt % to 80 wt % of the saliva promoter relative to the total weight of the efficacy layer.
[0022] In addition, according to one embodiment of the present invention, the adhesive layer comprises 2 wt % to 50 wt % of the total weight.
[0023] In addition, according to one embodiment of the present invention, the functional layer comprises 20 wt % to 85 wt % of the total weight.
[0024] In addition, according to an embodiment of the present invention, the strength of the oral preparation is greater than or equal to 1000 gf and less than 4000 gf.
[0025] Furthermore, according to one embodiment of the present invention, the oral preparation further includes a layer that performs at least one function selected from the group consisting of surface coating, dissolution rate adjustment, strength adjustment, tooth surface polishing, whitening, and pH adjustment.
[0026] According to one embodiment of the present invention, there is provided an oral adhesive composition, wherein at least one polymer selected from the group consisting of a mixture of tapioca starch without linamarin and chicory dietary fiber is used as an oral adhesive.
[0027] Effects of the Invention
[0028] The oral adhesive composition of the present invention, which contains at least one selected from the group consisting of a mixture of tapioca starch from which linamarin has been removed and chicory dietary fiber, can reduce irritation to the oral mucosa and has excellent adhesiveness.
[0029] In addition, the oral preparation containing the oral adhesive composition has low irritation to the oral mucosa and exhibits high adhesion to the oral mucosa even when saliva secretion is high, so it is excellent in usability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an image of an oral preparation according to one example of the present invention.
[0031] Figure 2 This is a schematic diagram showing a method for detecting the hydrophilicity of silica contained in the oral preparation according to one embodiment of the present invention.
[0032] Figure 3 : is an image of a test process for detecting the adhesion of the oral preparation according to one embodiment of the present invention.
[0033] Figure 4 : is an image of a test process for checking the strength of the oral preparation according to one embodiment of the present invention.
[0034] Figure 5 This is a graph comparing the adhesiveness of the oral preparation according to one example of the present invention.
[0035] Figure 6 This is a graph comparing the neutralization rates of VSCs with and without the oral halitosis suppressant of an oral preparation according to one example of the present invention.
[0036] Figure 7 This is a graph comparing the disintegration rates of the oral preparations according to one example of the present invention. DETAILED DESCRIPTION
[0037] The present invention will be described in more detail below by way of examples. These examples are provided to describe the present invention in more detail, but the scope of the present invention is not limited to these examples.
[0038] The present invention can be implemented in various changes and can have various forms, so specific embodiments are illustrated in the drawings and described in detail in the text. However, this does not limit the present invention to a specific disclosed form, and the present invention includes all changes, equivalents and even substitutes within the scope of the concept and technology of the present invention.
[0039] When describing the various drawings, similar symbols are used for similar constituent elements. In the drawings, in order to more clearly describe the present invention, the size of the structure is enlarged and shown compared to the actual size. The terms first, second, etc. are used to describe various constituent elements, and the above terms do not have a limiting effect on the above constituent elements. The above terms are only used to distinguish one constituent element from other constituent elements. For example, without departing from the scope of the claims of the present invention, the first constituent element may be named the second constituent element, and similarly, the second constituent element may be named the first constituent element. In the absence of a clear indication of different meanings in the text, the expression of the singular includes the meaning of the plural.
[0040] In this application, the terms "including" or "having" indicate the existence of features, numbers, steps, actions, constituent elements, components or combinations thereof recorded in the specification, and do not preclude the existence or additional possibility of one or more other features or numbers, steps, actions, constituent elements, components or combinations thereof. In addition, when a layer, film, region, plate or other part is mentioned as being "on" another part, this includes not only the case where the other part is "directly above" the other part, but also the case where the other part exists in between.
[0041] In addition, in this specification, when it is mentioned that a certain layer, film, region, plate, etc. is formed on other parts, the direction of the formation is not limited to the upper direction, but also includes the case where it is formed in the side or lower direction. Conversely, when it is mentioned that a layer, film, region, plate, etc. is "below" other parts, this includes not only the case where it is "directly below" other parts, but also the case where there is another part in between.
[0042] According to one embodiment of the present invention, there is provided an oral preparation, comprising: an adhesive layer comprising an adhesive polymer; and a functional layer, wherein the adhesive polymer comprises at least one selected from the group consisting of a mixture of cassava starch with linamarin removed and chicory dietary fiber.
[0043] In addition, according to one embodiment of the present invention, an oral preparation is provided, wherein the above-mentioned efficacy layer provides at least one of the functions of inhibiting bad breath, promoting saliva secretion, reducing dental plaque, reducing gingivitis, reducing periodontitis, alleviating periodontal diseases and alleviating caries. In the case of carboxymethyl cellulose (CMC), carbopol (polyacrylic acid), and polyvinyl pyrrolidone (PVP), which are known as adhesive components used in the prior art, ionic interactions occur between the synthetic polymers used as adhesives and the oral mucosa, thereby causing the problem of mucosal pain. Acaciagum, a natural polymer used for adhesives as another corresponding solution, also contains carboxyl groups (-COOH), so the problem of ionic interactions with the oral mucosa cannot be solved. In contrast, the natural adhesive polymer contained in the oral preparation of one embodiment of the present invention, i.e., a mixture of cassava starch without linamarin and chicory dietary fiber, does not contain a carboxyl group (-COOH), does not produce ionic interaction with the oral mucosa, and has an adhesion force that is similar to or superior to that of generally known adhesive polymers. When the adhesive preparation is used for a long time to suppress or relieve bad breath, the irritation to the oral mucosa is reduced.
[0044] In addition, the oral preparation of one embodiment of the present invention can adjust the dissolution rate. 3 ) and citric acid and can be provided in the form of an effervescent tablet, and can also contain a hydrophilic component such as salt or sugar. In addition, the binder content can be increased to delay the dissolution rate, and the oral preparation of one embodiment of the present invention can be used for 1 hour to a maximum of 4 hours.
[0045] According to one embodiment of the present invention, the oral preparation may be in the form of a double-layer tablet.
[0046] Figure 1 This is an image of an oral preparation according to one example of the present invention.
[0047] Reference Figure 1 The oral preparation comprises an adhesive layer containing an adhesive polymer and an efficacy layer providing functions such as halitosis suppression, saliva secretion promotion, and antibacterial. Figure 1 As shown, the oral preparation may be constructed as a double layer, but is not limited thereto.
[0048] The diameter of the oral preparation of one embodiment of the present invention is 5 mm to 16 mm, preferably 7 mm to 14 mm, more preferably 9 mm to 12 mm, and the thickness is 2 mm to 6 mm, preferably 2.5 mm to 5 mm, more preferably 3 mm to 4 mm. In the case of a diameter of 5 mm or less, it is inconvenient to use due to its small size. In the case of a diameter of 16 mm or more, the part that is separated from the gums is large, so it is difficult to attach. In addition, in the case of a thickness of 2 mm or less, the strength is low and it breaks, making it difficult to achieve tableting. When the thickness is 6 mm or more, it is too thick and inconvenient to use.
[0049] Based on the total double-layer weight, the content of the adhesive layer raw material is 0.5% to 60%, preferably 1% to 55%, more preferably 2% to 50%, and may include adhesive polymers, excipients, adhesives, lubricants, etc.
[0050] As the "adhesive polymer", a mixture of chicory dietary fiber or tapioca starch (cassava flour) from which linamarin has been removed can be used.
[0051] Chicory dietary fiber is a substance extracted from chicory plants (roots, etc.) through enzyme treatment or hot water treatment. It is a polysaccharide from the human body that is not decomposed by digestive enzymes, including inulin and oligofructose with a degree of polymerization of 2 to 60. Representative raw materials include inulin (Orafti GR) from Beneo (Germany).
[0052] Tapioca starch refers to starch extracted from cassava roots, and is a white powder rich in amylopectin as a raw material for removing linamarin. As a representative raw material, there are tapioca starch (Tapioca starch) of Sanguan Wongse Industries Co., Ltd. (Thailand). Linamarin is a cyanogenic glucoside found in the leaves and roots of plants such as cassava, snow peas, and flax. It is a kind of plant poison as a glycoside compound containing cyanogenic residues. It is stable in itself and harmless to the human body, but when hydrolyzed, it generates cyano groups and shows toxicity. Generally, it exists in the part that is not eaten, and it also exists in a part of the part that is eaten, and in the case of cassava, it exists in a considerable amount in the roots and leaves. In this regard, the present invention removes linamarin in cassava starch, thereby eliminating the dangerous elements of dietary exposure to linamarin.
[0053] The content of the adhesive polymer is 0.5% to 80% relative to the total weight of the adhesive layer raw material, preferably 10% to 70%, and more preferably 20% to 60%. As a binder for adjusting the adhesive force of the adhesive polymer and increasing the bonding force of the adhesive layer, it may include one or more gelatin, alginate, pectin, starch, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl acid, carboxymethyl cellulose, etc., and the total amount of the adhesive layer includes the content of the adhesive polymer, excipients, pH adjusters, lubricants, etc.
[0054] According to one embodiment of the present invention, the adhesive layer further comprises silicon dioxide as an excipient, and the oral preparation has any dosage form selected from the group consisting of a halitosis remover, a dry mouth relieving agent, a solid oral cleaning agent, a solid toothpaste, and a sustained-release candy. "Excipients" generally include calcium carbonate (CaCO 3 ), calcium sulfate (CaSO 4 ), calcium phosphate (CaPO 4 ), starch, etc., and contains silicon dioxide in order to strengthen the strength of the two-layer preparation and to increase the adhesion of the adhesive layer under conditions with a lot of saliva. Here, silicon dioxide refers to silicon dioxide particles with a hydrophilic surface, including precipitated silicon dioxide, pyrogenic silicon dioxide, colloidal silicon dioxide, etc. in the manufacturing method.
[0055] In addition, the content of the excipient is 1wt% to 60wt%, preferably 10wt% to 50wt%, and more preferably 20wt% to 40wt% relative to the total weight of the adhesive layer raw material. When the excipient is contained in an amount less than 1wt% relative to the total weight of the adhesive layer raw material, the strength enhancement effect and the adhesion enhancement effect under the condition of a large amount of saliva are weak, and when the excipient is contained in an amount exceeding 50wt%, it is difficult to perform manufacturing and mixing during the tableting process due to a large amount of dust.
[0056] Figure 2This is a schematic diagram showing a method for detecting the hydrophilicity of silica contained in an oral preparation according to an embodiment of the present invention. Here, hydrophilicity refers to a substance in which, after a tangent is drawn at a point where a silica particle at a horizontal interface of water and oil (a solvent that is not miscible with water) intersects the interface, the angle formed by the tangent and the water on the interface is 0 degrees to 90 degrees, preferably 5 degrees to 85 degrees, and more preferably 10 degrees to 80 degrees.
[0057] In addition, the diameter of the silica particles is 1 nm to 50 μm, preferably 1.5 nm to 40 μm, and more preferably 2 nm to 30 μm. When the diameter of the silica particles is less than 1 nm, it is difficult to handle due to dust during manufacturing, and there is a problem of weakened bonding strength. When the diameter of the silica particles is 50 μm or more, the strength enhancement and adhesion enhancement effects are weak.
[0058] "Lubricant" can be added to facilitate the compression and tablet discharge process during manufacturing. As lubricant raw materials, calcium stearate, magnesium stearate, stearic acid, sodium stearyl fumarate, talc, etc. can be used. Based on the adhesive layer raw material, the content is 0.1% to 10%, preferably 0.3% to 7%, and more preferably 0.5% to 5%. Based on the adhesive layer raw material, if the content of the lubricant exceeds 10%, the adhesion force decreases. If the content of the lubricant is less than 0.1%, it will be difficult to make tablets due to friction.
[0059] Based on the weight of the entire double layer, the weight of the raw material of the functional layer is 10% to 95%, preferably 15% to 90%, more preferably 20% to 85%, and further preferably 50% to 70%, and may include, but not limited to, a bad breath suppressant, a saliva secretion promoting component, an excipient, an adhesive, a lubricant, etc. Based on the weight of the entire double layer, when the weight of the functional layer exceeds 90%, the adhesion decreases, and when the weight of the functional layer is less than 10%, the efficacy is weak.
[0060] The functional layer may be formed as a plurality of layers instead of a single layer. In addition, when the functional layer is formed as a plurality of layers, each functional layer may perform different functions from each other, or layers performing the same function may be separated.
[0061] According to one embodiment of the present invention, an oral preparation is provided, wherein the functional layer further comprises copper ions (Cu 2+), zinc ion (Zn 2+ ) or tin ions (Sn 2+ ) is any one or more of the group consisting of salts thereof.
[0062] "Bad breath suppressants" are ingredients that have a VSCs neutralizing effect or an antibacterial effect on VSCs-producing bacteria. 2- and CH 3 S - Such strong ion binding force of sulfides inhibits the volatilization of VSCs. VSCs-producing bacteria refer to bacteria that produce VSCs including Porphyromonas gingivalis (P. gingivalis), Fusobacterium nucleatum (F. nucleatum), Tannerella forsythus (T. forsythus), Prevotella intermedia (P. intermedia), and Prevotella nigrescens (P. nigrescens).
[0063] As a bad breath suppressant, one or more copper ions (Cu 2+ ), zinc ion (Zn 2+ ), tin ions (Sn 2 + ) The content of ionic salts is 0.01% to 10%, preferably 0.05% to 7%, more preferably 0.1% to 5%, based on the raw materials of the functional layer, and preferably within the daily recommended intake amount.
[0064] In the presence of the above-mentioned bad breath inhibitor, copper ions (Cu 2+ ), zinc ion (Zn 2+ ), tin ions (Sn 2+ ) in the case of S 2- and CH 3 S - The strong binding force of such sulfides can inhibit the formation of VSCs. 2+ ) oral preparations can show antibacterial effects.
[0065] The oral preparation produced by including the above-mentioned bad breath suppressant can continuously release the above-mentioned effective ingredient in the oral cavity, thereby increasing its effect.
[0066] The copper ion (Cu 2+) can include a salt selected from the group consisting of acetylmethionine copper (Copper Acetylmethionate), acetyltyrosinate copper methylsilanol (Copper Acetyl Tyrosinate Methylsilanol), ascorbyl phosphate copper succinoyl tripeptide-34 (Copper Ascorbyl Phosphate Succinoyl Tripeptide-34), copper aspartate (Copper Aspartate), copper carbonate hydroxide (Copper Carbonate Hydroxide), chlorophyll copper (CopperChlorophyll), copper chloride (Copper Chloride), copper citrate (Copper Citrate), copper DNA (CopperDNA), copper gluconate (Copper Gluconate), copper heptapeptide-14 pantothenate (Copper Heptapeptide-14 Pantothenate), copper lysinate / prolinate (Copper Lysinate / Prolinate), copper palmitoyl heptapeptide-14 (Copper Palmitoyl Heptapeptide-14), copper PCA (Copper PCA), PCA methylsilanol copper salt (Copper PCA Methylsilanol), Copper Picolinate, Copper Sulfate, Copper Tetrapeptide-52 Dimer, Copper Tripeptide-1, Copper Tripeptide-34HCl, Copper Tripeptide-1 Palmitamide, Disodium EDTA-Copper, etc.
[0067] The above zinc ion (Zn 2+) can include a salt selected from the group consisting of zinc acetate, zinc adenosine triphosphate, zinc adenosine triphosphate hydroxide, zinc ascorbate, zinc ascorbate hydroxide, zinc aspartate, zinc borate, zinc carbonate, zinc carbonate hydroxyl, zinc carboxydecyl trisiloxane, zinc chloride, zinc chloride hydroxide, zinc citrate, zinc coceth sulfate, zinc coco-sulfate, zinc cysteine, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, zinc bismuth sulfate, Cysteinate, Zinc Dibutyldithiocarbamate, Zinc Dimethicone PEG-25 Phthalate, Zinc Dimethicone PEG-8 Succinate, Zinc DNA, Zinc Formaldehyde Sulfoxylate, Zinc Glucoheptonate, Zinc Gluconate, Zinc Glutamate, Zinc Glycinate, Zinc Glycinate Salicylate, Zinc Glycyrrhetinate, Zinc Hydrolyzed Collagen, Zinc Hydrolyzed Hyaluronate Hyaluronate, Zinc Indoleacetate Hydroxide, Zinc Lactate, Zinc Laurate, Zinc Magnesium Aspartate, Zinc MyristateMyristate, Zinc Neodecanoate, Zinc Nitrate, Zinc Oxide, Zinc Palmitate, Zinc Palmitoyl Nonapeptide-14, Zinc PCA, Zinc Pentadecene Tricarboxylate, Zinc Peroxide, Zinc Phenolsulfonate, Zinc Picolinate, Zinc Pyrithione, Zinc Ricinoleate, Zinc Rosinate, Zinc Salicylate, Zinc Stearate, Zinc Undecylenate, Zinc Undecylenoyl Hydrolyzed Wheat Protein Protein) etc.
[0068] The above tin ions (Sn 2+ ) may include tin oxide (Tin Oxide) and the like.
[0069] In addition to the above-mentioned ingredients, the efficacy layer may further contain antibacterial ingredients such as chlorhexidine, cetylpyridinium chloride, triclosan, essential oils, chlorine dioxide, green tea catechins, hinokitiol, lactoferrin, lactoperoxidase, etc., in order to enhance the efficacy of the bad breath suppressant. The content of the above-mentioned antibacterial ingredients is 0.01% to 10%, preferably 0.05% to 7%, and more preferably 0.1% to 5%, based on the raw materials of the efficacy layer.
[0070] The "saliva secretion promoting component" is a component that stimulates the salivary glands to promote saliva secretion, and includes sugars, sweeteners, ascorbic acid, malic acid, citric acid, etc., and preferably includes xylitol. Based on the raw materials of the functional layer, the content of the sugar secretion promoting component is 30% to 95%, preferably 40% to 90%, and more preferably 50% to 85%.
[0071] "Lubricant" can be added to facilitate compression and tablet discharge during the manufacturing process. Lubricant raw materials may include calcium stearate, magnesium stearate, stearic acid, sodium stearyl fumarate, and talc. Based on the raw materials of the functional layer, the content of the lubricant is 0.1% to 10%, preferably 0.3% to 7%, and more preferably 0.5% to 5%.
[0072] The functional layer includes at least one selected from the group consisting of gelatin, alginate, pectin, starch, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and polyvinyl acid as a binder. Based on the functional layer raw material, the content of the binder is 0.1% to 20%, preferably 3% to 17%, and more preferably 5% to 15%.
[0073] Furthermore, the functional layer or the adhesive layer may contain sweeteners such as stevia and saccharin for flavor enhancement, and flavoring agents such as peppermint oil and menthol for aroma enhancement.
[0074] The oral preparation of one embodiment of the present invention has a strength of 1000 gf or more and less than 4000 gf. If the strength is less than 1000 gf, the preparation may be damaged during the manufacturing process or during transportation, and if the strength exceeds 4000 gf, the preparation may be difficult to ingest.
[0075] The oral preparation according to one embodiment of the present invention further comprises a layer that performs at least one function selected from the group consisting of surface coating, dissolution rate adjustment, strength adjustment, tooth surface grinding, whitening, and pH adjustment. In addition, the layer that performs the above functions may be composed of multiple layers.
[0076] Experimental Example 1. Comparison of Adhesion and Strength of Oral Preparations Based on Adhesive Polymers
[0077] Preparation Example 1. Preparation of Comparative Examples 1 to 4 and Examples 1 to 3
[0078] When manufacturing the adhesive layer for testing strength, the same raw materials were used as common components, namely, excipients, pH adjusters, binders, and lubricants. Calcium carbonate (CaCO 3 ), sodium bicarbonate (NaHCO 3 ), Hydroxypropyl Methylcellulose (HPMC) was used as a binder, and Magnesium Stearate was used as a lubricant.
[0079] The tablet manufacturing method is as follows: In each manufacturing example, the corresponding raw materials were put into a powder mixer and mixed for more than 30 minutes. After that, 300 mg of the mixed raw materials were placed in a circular mold with a diameter of 12 mm and a pressure of 5 mPa was applied using a hydraulic press (Qmesys, QM900A) to obtain the tablet.
[0080] Experimental Example 1-1. Adhesion Test of Oral Preparations Based on Adhesive Polymers
[0081] Figure 3 : is an image of a test process for detecting the adhesion of the oral preparation according to one embodiment of the present invention.
[0082] The adhesion test was conducted under normal conditions and under conditions with a lot of saliva. The test under normal conditions refers to the test being conducted after removing 0.5 g of water from the gel (Gel) to prevent drying using a micropipette, and the test under conditions with a lot of saliva refers to the test being conducted without removing 0.5 g of water.
[0083] The adhesion of the prepared oral preparation samples was measured by referring to the literature (Annika Borde and three others, Journal of Colloid and Interface Science 341 (2010) 255-260) using an oral mucosal yarn material to measure the force required to drop the oral preparation from the material.
[0084] First, 1% agarose gel was selected as the material for the oral mucosal yarn. After 1% agarose was dissolved in distilled water at high temperature, it was placed in a 10g gel solution prepared in a 50mm diameter Petri dish and then solidified at room temperature. After that, 0.5g of water was added to prevent the gel surface from drying out and stored.
[0085] The test used a physical property analyzer (product name: Texture Analyzer, manufacturer: TA instrument (American Thermal Analysis Instrument Company), model: TA.XT plus) and a 35mm aluminum probe (Probe). After the tablet was fixed to the probe tip using double-sided tape, a force of 50gf was applied to the tablet on the surface of 1% agarose gel fixed on the ground for 30 seconds. The force when dropping was then divided by the tablet area to calculate the force per unit area (g / mm 2 ), thereby obtaining the adhesion of the sample. At this time, in order to improve the accuracy of the detection value, after manufacturing 5 samples in each manufacturing example, the average adhesion was detected and recorded according to each manufacturing example.
[0086] Experimental Example 1-2. Strength test of oral preparations based on adhesive polymers
[0087] Figure 4 : is an image of a test process for checking the strength of the oral preparation according to one embodiment of the present invention.
[0088] The strength test of the manufactured oral preparation is carried out in accordance with the crush test method. The manufactured oral preparation is placed vertically on the ground (the round surface is perpendicular to the ground), and then the pressure (gf) applied per unit time is detected using a physical property analyzer (product name: Texture analyser, manufacturer: TA instrument, model: TA.XT plus) and a 35mm aluminum probe (Probe), and the strength is calculated by the value of the maximum force detected at the time of rupture. At this time, in order to improve the accuracy of the test value, the average strength is detected after manufacturing 5 samples in each manufacturing example, and the strength is recorded for each sample.
[0089]
Table 1
[0090]
[0091] Referring to Table 1, the experimental results show that the dosage forms of Examples 1 to 3 have higher strength and adhesion than the comparative example, and the degree of reduction in adhesion is smaller under the condition of more saliva.
[0092] Experimental Example 2. Comparison of strength and adhesion of oral preparations based on excipients
[0093] Preparation Example 2. Preparation of Comparative Example 2, Comparative Example 5, Comparative Example 6 and Examples 4 to 7
[0094] When manufacturing the adhesive layer for testing strength, the pH adjuster, adhesive, lubricant, and adhesive polymer as common components all use the same raw materials, and sodium bicarbonate (NaHCO 3 ), as a binder, hydroxypropyl methylcellulose (HPMC) was used, as a lubricant, magnesium stearate (Magnesium Stearate) was used, and as an adhesive polymer, carboxymethyl cellulose (CMC) was used.
[0095] The preparation method of oral preparation is as follows: In each preparation example, the corresponding raw materials are put into a powder mixer and mixed for more than 30 minutes. Then, 300 mg of the mixed raw materials are put into a circular mold with a diameter of 12 mm and a pressure of 5 mPa is applied using a hydraulic press (Qmesys, QM900A) to prepare.
[0096] When the manufactured oral preparation was not subjected to a separate drying step, it was placed in a container containing silica for drying and stored. Then, the strength and adhesion of each manufacturing example were tested.
[0097] The experiment was conducted to test the strength and adhesion of oral preparations using different excipients.
[0098]
Table 2
[0099]
[0100] Referring to Table 2, the experimental results show that Examples 4 to 7 have higher dosage form strength and higher adhesion under normal conditions and under conditions with a lot of saliva than Comparative Examples 1 and 5. In particular, in the case of excipients with silica particles having a size of 50 μm or more, as in Comparative Example 6, the strength enhancement and adhesion enhancement effects were not obtained.
[0101] Experimental Example 3: Using chicory dietary fiber or cassava starch from which linalin was removed as an adhesive polymer Comparison of strength and adhesion of oral preparations using silicon dioxide as an excipient
[0102] Preparation Example 3. Preparation of Examples 8 and 9
[0103] When manufacturing the adhesive layer for testing strength, the pH adjuster, adhesive, and lubricant as common components all used the same raw materials. Sodium bicarbonate (NaHCO 3), Hydroxypropyl Methylcellulose (HPMC) was used as a binder, and Magnesium Stearate was used as a lubricant.
[0104] The oral preparation was prepared as follows: In each preparation example, the corresponding raw materials were put into a powder mixer and mixed for more than 30 minutes. Then, 300 mg of the mixed raw materials were placed in a circular mold with a diameter of 12 mm and a pressure of 5 mPa was applied using a hydraulic press (Qmesys, QM900A).
[0105] When the manufactured oral preparation was not subjected to a separate drying step, it was placed in a container containing silica for drying and stored. Then, the strength and adhesion of each sample were tested.
[0106] The experiment was performed in the same manner as that performed in Experimental Example 1.
[0107]
Table 3
[0108] Comparative Example 1 Example 8 Example 9 <![CDATA[CaCO 3 ]]> 32 0 0 25μm silica 0 32 32 <![CDATA[NaHCO 3 ]]> 5 5 5 HPMC 10 10 10 Magnesium Stearate 3 3 3 CMC 50 0 0 Chicory Dietary Fiber 0 50 0 Tapioca starch 0 0 50 Tablet strength (gf) 71.3 2844.3 1787.6 <![CDATA[Adhesion under general conditions (gf / mm 2 )]]> 0.318 0.403 0.431 <![CDATA[Adhesion force under the condition of excessive saliva (gf / mm 2 )]]> 0.244 0.380 0.470
[0109] Figure 5 Graph comparing the adhesiveness of the oral preparations of one embodiment of the present invention. Figure 5 As shown in Table 3, the experimental results show that compared with Comparative Example 1, the strength and adhesion of Examples 8 and 9 are higher. In particular, even when the excipient is changed to silicon dioxide compared with Examples 1 and 2, the strength and adhesion are improved.
[0110] Experimental Example 4. Comparison of irritation to oral mucosa based on adhesive polymers
[0111] Preparation Example 4. Preparation of Comparative Examples 7 to 10 and Examples 10 to 11
[0112] In order to compare based on each adhesive polymer, in the case of the comparative example, it is composed of carboxymethyl cellulose (CMC), polyvinyl pyrrolidone (PVP), carbopol (Carbopol, Polyacryli cacid), and gum arabic gum, and in the case of the embodiment, it is composed of chicory dietary fiber or tapioca starch.
[0113] In order to confirm the irritation to the oral mucosa in the experiment, the irritation was compared by cytotoxicity evaluation. The cytotoxicity evaluation is as follows: V79-4 cells (Chinese Hamster, CCL of lung tissue fibroblasts) were cultured for 24 hours, and then each adhesive polymer was diluted to an appropriate concentration (any concentration between 1% and 10%) in a dilutable solvent (culture medium (3% FBS), phosphate buffered saline (DPBS), dimethyl sulfoxide (DMSO)). Then, the cells were cultured in culture medium with the original solution or treated at 1 / 100 for 24 hours, and then the absorbance was detected using MTT reagent to determine the viability of the cells for toxicity evaluation. From the results, IC50 (Half maximal inhibitory concentration: half inhibition concentration) and CTI (Cellular Toxicity index: cytotoxicity index) representing 50% cell killing concentration were calculated.
[0114]
Table 4
[0115]
[0116] Referring to Table 4, Example 10 and Example 11 had higher IC50 values than Comparative Examples 7 to 10, showing lower toxicity, thereby confirming that the CTI was extremely low.
[0117] Experimental Example 5. Based on zinc ion (Zn 2+ ) and copper ions (Cu 2+ ) added to oral preparations to improve bad breath Compare
[0118] Preparation Example 5. Preparation of Comparative Examples 11 to 12 and Examples 12 to 13
[0119] As shown in Table 5, the oral preparations used for evaluating the effect of improving bad breath used the same raw materials as common components, namely, excipients, flavor enhancers, pH adjusters, binders, and lubricants during production. As excipients, xylitol was used in the upper layer, and calcium carbonate (CaCO) was used in the lower layer. 3 ), as a flavor enhancer, sodium saccharin, L-menthol, and mint tea extract powder were used alone in the upper layer, and as a pH adjuster, sodium bicarbonate (NaHCO 3 ), as a binder, hydroxypropyl methylcellulose (HPMC) was used, and as an IE lubricant, magnesium stearate was used.
[0120]
Table 5
[0121]
[0122] The oral preparation manufacturing method is as follows: In each manufacturing example, the corresponding layer raw materials are put into a powder mixer according to the ratio described in the above table and mixed for more than 30 minutes. Then, 50 mg of the mixed lower layer raw materials are put into a circular mold with a diameter of 12 mm and then flattened, and then 300 mg of the upper layer raw materials are put into the mold, and a pressure of 5 mPa is applied using a hydraulic press (Qmesys, QM900A) to prepare.
[0123] When the manufactured oral preparation was not subjected to a separate drying step, it was placed in a container containing silica for drying and stored.
[0124] Experimental Example 5-1. Based on zinc ion (Zn 2+ ) and copper ions (Cu 2+ Comparison of VSC neutralization effects of oral preparations with addition of
[0125] The experiment was conducted to evaluate the neutralization effect of VSC (Volatile Sulfide Compounds) after manufacturing an oral preparation for improving bad breath. 100 μl of the odor source sample (containing about 1250 ppb of H 2 S, about 1000 ppb MeSH) were placed in a sealed 10 ml head space vial, and then 1 g of a 25% tablet suspension obtained by dissolving the tablets in pure water according to each manufacturing example was added. Then, after standing for 3 minutes, H was detected using a breath detector (Oralchroma, Abimedical, Abilit Corp.). 2 The concentrations of S and MeSH.
[0126]
Table 6
[0127] Neutralization rate (%) Comparative Example 11 Comparative Example 12 Example 12 Embodiment 13 <![CDATA[H 2 S]]> 90.13 85.41 99.64 99.15 MeSH 15.42 19.72 93.52 96.43
[0128] Figure 6 Graph comparing the neutralization rate of VSC according to the presence or absence of the oral halitosis suppressant of an example of the present invention. Figure 6 As shown in Table 6, Examples 12 and 13 have higher halitosis improving effects than Comparative Examples 11 and 12.
[0129] Experimental Example 5-2. Based on zinc ion (Zn 2+ ) and copper ions (Cu 2+ Comparison of VSC neutralization rates under actual use conditions of oral preparations containing )
[0130] After manufacturing the oral preparation, the oral preparation was manufactured under actual use conditions, and then the VSC neutralization rate was measured under actual use conditions, and the halitosis improving effect was evaluated. Different types of samples were distributed to 28 evaluators randomly divided into 4 groups, and they were asked to take the oral preparation twice a day. The oral preparation for halitosis improvement was taken for 4 weeks, the VSC neutralization rate was measured every week, and the reduction rate of 4 types of halitosis-inducing bacteria was measured after 4 weeks, thereby evaluating the halitosis improving effect.
[0131] The VSC oral malodor detector (Oralchroma, Abimedical, AbilitCorP.) was used to detect H at the time point of 0 week after the start of the experiment. 2 S and MeSH concentrations, and then detect H 2 S and MeSH concentrations, and the neutralization rate was calculated using the following formula.
[0132]
[0133]
Table 7
[0134]
[0135] Referring to Table 7, Examples 12 and 13 showed higher VSC neutralization rates under actual use conditions than Comparative Examples 11 and 12. Therefore, it can be confirmed that Examples 12 and 13 have higher halitosis-reducing effects than Comparative Examples 11 and 12.
[0136] Experimental Example 5-3. Based on zinc ion (Zn 2+ ) and copper ions (Cu 2+ Comparison of the reduction rate of halitosis-causing bacteria under actual use conditions of oral preparations containing )
[0137] After manufacturing the oral preparation, the reduction rate of bad breath-inducing bacteria was detected under actual use conditions to evaluate the bad breath improvement effect. In order to detect the reduction rate of bad breath-inducing bacteria, an experiment was conducted by the following method. At the beginning of the experiment, in order to quantitatively evaluate each strain in the oral cavity, the subjects rinsed their mouths for one minute to obtain an oral rinse (LG Household & Health Care Simple Perio), and then the oral microorganisms of the subjects were quantitatively analyzed by PCR analysis using the oral rinse. In addition, after taking the oral preparation for 4 weeks, the subjects also rinsed their mouths for 1 minute with an oral rinse (LG Household & Health Care Simple Perio), and then the oral microorganisms of the subjects were quantitatively analyzed by PCR analysis using the oral rinse. Then, the reduction rate of bad breath-inducing bacteria was obtained by the following formula.
[0138]
[0139]
Table 8
[0140]
[0141] Referring to Table 8, with respect to the four types of halitosis-inducing bacteria, Examples 12 and 13 showed higher halitosis-inducing bacteria reduction rates under actual use conditions than Comparative Examples 11 and 12. Therefore, it can be confirmed that Examples 12 and 13 have higher halitosis-improving effects than Comparative Examples 11 and 12.
[0142] Experimental Example 6. Evaluation of the use satisfaction and oral irritation of oral preparations based on adhesive polymers experiment
[0143] Preparation Example 6. Preparation of Comparative Examples 13 to 16 and Examples 12 to 13
[0144] When manufacturing oral preparations for sensory evaluation, the common ingredients of excipients, flavor enhancers, pH adjusters, binders, and lubricants were all made from the same raw materials. As excipients, xylitol was used in the upper layer, and calcium carbonate (CaCO) was used in the lower layer. 3 ), as flavor enhancers, sodium saccharin, L-menthol, and mint tea extract powder were used alone in the upper layer, and as pH adjusters, sodium bicarbonate (NaHCO 3 ), Hydroxypropyl Methylcellulose (HPMC) was used as a binder, and Magnesium Stearate was used as a lubricant.
[0145] The oral preparation was prepared as follows: the corresponding layer raw materials of each preparation example were put into a powder mixer and mixed for more than 30 minutes according to the ratios described in the above table. Thereafter, 50 mg of the mixed lower layer raw materials were put into a circular mold with a diameter of 12 mm and the mold was flattened, and then 300 mg of the upper layer raw materials were put into the mold, and then a hydraulic press (Qmesys, QM900A) was used to apply a pressure of 5 mPa to prepare the preparation.
[0146] When the manufactured oral preparation was not subjected to a separate drying step, it was placed in a container containing silica for drying and stored.
[0147] The experiment was conducted by manufacturing oral preparations for improving bad breath with different adhesive polymers and then evaluating the satisfaction with use and oral irritation. Different types of samples were distributed to 30 evaluators randomly divided into 6 groups, and then they were asked to take the oral preparations twice a day. After using it for 1 week, a sensory evaluation of fragrance, taste, irritation, and refreshing feeling was conducted. The evaluation was given from the lowest score of 0 to the highest score of 5, and the average of the subjects' response values was calculated, and a score was obtained for each item.
[0148]
Table 9
[0149]
[0150] Referring to Table 9, the results of the sensory evaluation show that in terms of aroma, taste, and freshness, Comparative Examples 13 to 16 and Examples 12 to 13 obtained similar evaluations, but in terms of reducing irritation, Examples 12 and 13 obtained higher scores than Comparative Examples 13 to 16. It can be seen that Examples 12 and 13 produce less irritation than Comparative Examples 13 to 16.
[0151] Experimental Example 7. Disintegration rate test of oral preparations based on adhesive polymers
[0152] Preparation Example 7. Preparation of Examples 14 to 15 and Preparation of Comparative Example 17
[0153] Regarding the oral preparations used to detect the disintegration rate, Comparative Example 17 used a product that dissolves after being attached to the oral mucosa (Oracoat Xylimelts, product usage time (dissolution rate): 1 to 4 hours during the day, 4 to 8 hours at night). In addition, in order to make the weight the same as the weight of one tablet of Comparative Example 17 (about 700 mg), Example 14 and Example 12 have the same composition, and Example 15 and Example 13 have the same composition, but 100 mg of adhesive layer raw materials and 600 mg of functional layer raw materials are used when tableting. Here, when manufacturing as shown in Table 9, the excipients, flavor enhancers, pH adjusters, adhesives, and lubricants used as common ingredients all use the same raw materials. As excipients, xylitol (Xylitol) is used in the upper layer, and calcium carbonate (CaCO) is used in the lower layer. 3 ), as flavor enhancers, sodium saccharin, L-menthol, and mint tea extract powder were used alone in the upper layer, and as pH adjusters, sodium bicarbonate (NaHCO 3 ), HydroxypropylMethylcellulose (HPMC) was used as a binder, and Magnesium Stearate was used as a lubricant.
[0154] The oral preparation manufacturing method is as follows: In each manufacturing example, the corresponding layer raw materials were put into a powder mixer according to the ratio described in Table 9 and mixed for more than 30 minutes. Then, 100 mg of the mixed adhesive layer raw materials were put into a circular mold with a diameter of 12 mm and flattened, and 600 mg of the upper layer raw materials were put into the mold, and then a hydraulic press (Qmesys, QM900A) was used to apply a pressure of 5 mPa to obtain the preparation.
[0155] When the manufactured oral preparation was not subjected to a separate drying step, it was placed in a container containing silica for drying and stored.
[0156] The experiment was conducted by manufacturing oral preparations for improving bad breath with different adhesive polymers and then testing the disintegration rate. After placing one preparation of Example 14, Example 15 and Comparative Example 17 in a tea bag net, the disintegration rate in 100 g of distilled water at 37°C was tested. For each preparation, the tea bag net was taken out of the distilled water after 1 hour, 2 hours, and 4 hours, and then dried in an oven at 60°C for 24 hours, and then its weight was tested, and the disintegration rate was calculated by the following formula.
[0157]
[0158]
Table 10
[0159] Time (h) Embodiment 14 Embodiment 15 Comparative Example 17 0 0 0 0 1 48.6 43.8 38.3 2 68.7 65.2 60.3 4 90.1 87.6 94.8
[0160] Figure 7 1 is a graph comparing the disintegration rates of oral preparations according to one embodiment of the present invention. Figure 7 As a result of evaluating the disintegration rate, it was confirmed that the disintegration rate was similar to that of Comparative Example 17. Compared with Comparative Example 17, the disintegration rates of Examples 14 and 15 were somewhat slower, which showed that the sustained-release effect of delaying the release of the effective ingredient and making the effect last was somewhat better.
[0161] The above description is made with reference to the preferred embodiments of the present invention, but a person skilled in the art or a person skilled in the art may make various modifications and changes to the present invention without departing from the scope of the idea and technical field of the present invention described in the claims below.
[0162] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification but should be defined according to the claims.
Claims
1. An oral preparation comprising: an adhesive layer comprising an adhesive polymer; and a functional layer, The adhesive polymer includes at least one selected from the group consisting of a mixture of tapioca starch from which linamarin is removed and chicory dietary fiber.
2. The oral preparation according to claim 1, wherein The functional layer provides at least one of the functions of inhibiting bad breath, promoting saliva secretion, reducing dental plaque, reducing gingivitis, reducing periodontitis, alleviating periodontal diseases, and alleviating dental caries.
3. The oral preparation according to claim 1, wherein The oral preparation has a double-layer tablet form.
4. The oral preparation according to claim 1, wherein The adhesive layer further comprises silicon dioxide as an excipient. The oral preparation has any one dosage form selected from the group consisting of a deodorant, a xerostomia alleviator, a solid oral cleaning agent, a solid toothpaste, and a sustained-release candy.
5. The oral preparation according to claim 4, wherein The above excipients are contained in an amount of 20 wt % to 40 wt % relative to the total weight of the adhesive layer material.
6. The oral preparation according to claim 4, wherein The diameter of the silica particles is not less than 1 nm and not more than 50 μm.
7. The oral preparation according to claim 1, wherein The functional layer further comprises, as a bad breath suppressant, an ion selected from copper ions (Cu 2+ ), zinc ion (Zn 2+ ) or tin ions (Sn 2 + ) is any one or more of the group consisting of salts thereof.
8. The oral preparation according to claim 7, wherein The efficacy layer contains the oral malodor suppressant in an amount of 0.1 wt % to 5 wt % relative to the total weight.
9. The oral preparation according to claim 1, wherein The efficacy layer contains 50 wt % to 80 wt % of the saliva promoting agent relative to the total weight of the efficacy layer.
10. The oral preparation according to claim 1, wherein The adhesive layer comprises 2 wt % to 50 wt % of the total weight.
11. The oral preparation according to claim 1, wherein The functional layer comprises 20 wt % to 85 wt % of the total weight.
12. The oral preparation according to claim 1, wherein The oral preparation has a strength of 1000 gf or more and less than 4000 gf.
13. The oral preparation according to claim 1, wherein The oral preparation further includes a layer that performs at least one function selected from the group consisting of surface coating, dissolution rate adjustment, strength adjustment, tooth surface polishing, whitening, and pH adjustment.
14. An oral adhesive composition, wherein: A polymer containing at least one selected from the group consisting of a mixture of tapioca starch from which linamarin is removed and chicory dietary fiber is used as an oral adhesive.